2016
DOI: 10.7863/ultra.15.05080
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Identified Echogenic Renal Masses Up to 1 cm in Size Are So Rarely Malignant They Can Be Safely Ignored

Abstract: chogenic renal masses in general are more often angiomyolipomas than carcinomas. Without regard to size, the chance of carcinoma in general is high enough that echogenic masses should not be ignored, and further workup is advocated. To this end, a recent review by Farrelly et al 1 concluded that "all noncalcified echogenic renal lesions detected with ultrasound need a CT to rule out a renal cell carcinoma." Another study further recommended computed tomography (CT) ORIGINAL RESEARCHObjectives-The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Itani et al found that subcentimetre echogenic renal lesions identified on US (containing fat or absence of growth for 5 years) were also likely benign enough not to require follow-up. 16 Further supporting evidence from Jinzaki et al demonstrated slow growth of AMLs at a rate of 5% or 19 mm per year, 7 a rate that was far slower in the present study population. Although the present study investigated definite reported AMLs, only 17 cases (0.01%) were found in which patients were suggested to have possible malignancies on their subsequent scans.…”
Section: Discussionsupporting
confidence: 87%
“…Itani et al found that subcentimetre echogenic renal lesions identified on US (containing fat or absence of growth for 5 years) were also likely benign enough not to require follow-up. 16 Further supporting evidence from Jinzaki et al demonstrated slow growth of AMLs at a rate of 5% or 19 mm per year, 7 a rate that was far slower in the present study population. Although the present study investigated definite reported AMLs, only 17 cases (0.01%) were found in which patients were suggested to have possible malignancies on their subsequent scans.…”
Section: Discussionsupporting
confidence: 87%
“…Our smallest oncocytic variant was 1.2 cm (Figure 4). Our data is similar to that of Itani et al 3 who found no RCCs among 120 echogenic renal masses less than 1 cm. We found no RCCs among any of our echogenic renal masses less than 1 cm in diameter.…”
Section: Discussionsupporting
confidence: 92%
“…From this, we included only patients who had a follow‐up unenhanced computed tomography (CT), contrast‐enhanced CT or MR imaging, pathologically proven diagnosis, or lesions that were stable (showed no growth) on follow‐up ultrasound performed more than 5 years after the initial examination (Figure 1). Itani et al 3 used no growth for 5 years as a criterion for a benign lesion in 66 of 120 of their benign lesions. Exclusion criteria included patients less than 18 years of age, those ultrasounds with less than 5 years of follow‐up, lesions that were primarily cysts, and lesions with characteristic ultrasound findings for nephrolithiasis such as shadowing and twinkling artifact.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations